INTERNET USAGE AND ECONOMIC DEVELOPMENT : EVIDENCE FROM A PANEL DATA - Das, Dr. Chandrabhanu; Nanga, Dr. RoopIatha (The journal of contemporary issues in business and government, 2022)
The advent of internet and telecommunication technology has led to the emergence of digital footprint around the world. Subsequently there have been studies linked to internet usage and socioeconomic development. The difference in internet usage among different countries has also been identified as digital divide. Policy makers and government are concerned about internet and telecommunication usage as drivers of digital economy for sustainable development goals. However, not all countries are similar in their level of internet penetration and usage of advanced technologies. Socioeconomic barriers prevalent in different countries may prevent much of the population engagement in different information and communication technologies. Therefore it becomes imperative to study from a wider perspective whether the economic development of nations influence the usage of digital technologies. This paper examines the impact of different economic development indicators on internet usage by applying different panel data analysis methods. The economic indicators evaluated here are GDP growth, proportion of salaried workers, unemployment levels, broad money, import of technology equipment, capital growth, mobile subscription, employment and income levels. All the factors except capital growth are having statistical significance with proportion of internet usage. Further, at different income levels the proportion of salaried workers has a significant influence on internet usage. The study reveals the importance of economic development in improving the digital footprint among different nations.